PENGARUH PARTISIPASI PEMAKAI TERHADAP KEPUASAN PEMAKAI DALAM PENGEMBANGAN SISTEM INFORMASI AKUNTANSI DENGAN KOMPLEKSITAS TUGAS DAN KOMPLEKSITAS SISTEM SEBGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur di Magelang) - Al, M Al; Rais, Dian Rais (Jurnal Analisis Bisnis Ekonomi, 2005)
This research aim to test influence of user participation to satisfaction of user which is dimoderasi by duty complexity and system complexity in development of accounting information system. Accountancy information system in resource corps had company to yield information required by internal side and eksternal, one of the yielded output in the form of information concerning processed financial statement of monetary transaction datas. Considering important role and existence of accounting information system. In change of accounting information system of manual system become computerization system [do] not only concerning change of technology but also change of behavior, is there for needed by existence of participation of user. Data type the used is obtained primary data through questionaire. Intake of sampel with technique of purposive sampling, this company sampel amount to 20 companies. Each; Every perusahaan asked to fill kuesioner addressed at 5 division manager that is personnel manager, produce, marketing, monetary and administration. Kuesioner which earn to be processed by only 51, utilizing to reach the target of this research was used by descriptive statistic, validity test and of reabilities, analyse simple regresi, test of anova, and test R-Square done constructively computer program of SPSS. Result examination of and validity of reabilitiesw show all datas in this research is valid and reliabel. In examination of the individually got by R-Square equal to 57,6% showing user participation in development of accounting information system give influence 57,6% to satisfaction of user, the rest 42,4% influenced by other variable. While at examination of the by is together got by R-Square equal to 56,6% to satisfaction of user, the rest 43,4% influenced by other variable. This reaearch result indicate that duty complexity do not as variable of moderating system complexity and are variable of moderating. This research support research of Chandrarin and Indriantoro (1997). Pursant to research result, suggested that by manufacturing business in Magelang entangle user in course of development of accounting information system so that lick lips with expected result.